1996
DOI: 10.1093/oxfordjournals.humrep.a019465
|View full text |Cite
|
Sign up to set email alerts
|

Andrology: Total antioxidant capacity of human seminal plasma

Abstract: Although the importance of seminal plasma in the protection of spermatozoa against reactive oxygen species is well known, only a few studies have investigated its antioxidative properties and the possible relationship between infertility and plasmatic antioxidant defences. The aim of the present study was to assess the status of the total non-enzymatic antioxidant defences of human seminal plasma. Semen samples were obtained from 101 patients consulting for infertility and 15 fertile donors. A total reactive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
83
0
3

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(92 citation statements)
references
References 8 publications
5
83
0
3
Order By: Relevance
“…Evidence has suggested that a low seminal Total Antioxidant Capacity (TAC) was related to the male infertility [14,[23][24][25]. The values for the TAC were significantly reduced in the subjects with impaired seminograms.…”
Section: The Routine Semen Analysismentioning
confidence: 99%
“…Evidence has suggested that a low seminal Total Antioxidant Capacity (TAC) was related to the male infertility [14,[23][24][25]. The values for the TAC were significantly reduced in the subjects with impaired seminograms.…”
Section: The Routine Semen Analysismentioning
confidence: 99%
“…20,27,28 However, it is unclear whether reduced semen antioxidant capacity necessarily causes sperm dysfunction (including sperm DNA damage). 1,3,29,30 Indeed, there is some controversy as to whether the high ROS levels detected in the semen of infertile men are due to increased ROS production, decreased ROS scavenging capacity or both.…”
Section: 14mentioning
confidence: 99%
“…6,15,16 Seminal plasma contains a number of high-molecular weight enzymatic antioxidants (superoxide dismutase, catalase and glutathione peroxidase) and a deficiency in these enzymes has been reported to cause sperm DNA damage and male infertility. 1,7,10, [17][18][19] Seminal fluid also contains non-enzymatic antioxidants (ascorbic acid, a-tocopherol, pyruvate, glutathione, Lcarnitine, taurine and hypotaurine) [20][21][22][23] which constitute the bulk of seminal antioxidant capacity. In addition, urate, 24 pyruvate, 11,25 albumin, beta carotenes and ubiquinol 26 have been detected in seminal plasma.…”
Section: Relationship Between Oxidative Stress and Sperm Dysfunctionmentioning
confidence: 99%
“…Some studies have shown that a deficiency in semen antioxidants is associated with sperm DNA damage, whereas, other studies have not observed such a relationship [6,[36][37][38][39]. Similarly, some studies have found that seminal antioxidant activity is reduced in infertile men with high levels of seminal ROS (relative to those with normal levels of ROS) whereas others have not shown this [14,[40][41][42]. To date, there are no studies to indicate a relationship between systemic antioxidant or vitamin deficiency and male infertility.…”
Section: Semen Antioxidants and Sperm Dna Damagementioning
confidence: 99%